2019
DOI: 10.1523/jneurosci.1954-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Oscillations in the Human Brain Implement Distractor Suppression Independent of Target Selection

Abstract: In principle, selective attention is the net result of target selection and distractor suppression. The way in which both mechanisms are implemented neurally has remained contested. Neural oscillatory power in the alpha frequency band (ϳ10 Hz) has been implicated in the selection of to-be-attended targets, but there is lack of empirical evidence for its involvement in the suppression of to-be-ignored distractors. Here, we use electroencephalography recordings of N ϭ 33 human participants (males and females) to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 63 publications
(69 reference statements)
10
93
0
1
Order By: Relevance
“…In accordance with previous studies suggesting a relation between alpha oscillations and the inhibition of irrelevant information (e.g. Bonnefond & Jensen, 2013;Händel et al, 2011;Rösner et al, 2020;Wöstmann et al, 2019), this alpha power increase might reflect the removal of mental representations of the interrupting arithmetic task from working memory after interruption processing had been completed (in the sense of an entire completion/closure of processing the interruption task). Importantly, in the high-demanding condition, alpha power in the resumption phase did not differ as a function of primary task performance and did not return to baseline level prior to retro-cue presentation (see figure 7).…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous studies suggesting a relation between alpha oscillations and the inhibition of irrelevant information (e.g. Bonnefond & Jensen, 2013;Händel et al, 2011;Rösner et al, 2020;Wöstmann et al, 2019), this alpha power increase might reflect the removal of mental representations of the interrupting arithmetic task from working memory after interruption processing had been completed (in the sense of an entire completion/closure of processing the interruption task). Importantly, in the high-demanding condition, alpha power in the resumption phase did not differ as a function of primary task performance and did not return to baseline level prior to retro-cue presentation (see figure 7).…”
Section: Discussionsupporting
confidence: 91%
“…The obtained Pearson correlation coefficients were averaged per time window, condition, and individual participants. data (Wöstmann et al, 2019). The dependent-samples non-parametric permutation test was furthermore used to compare the neural encoding accuracy derived from the entire sTRF across conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, alpha lateralization is thought of as a neural implementation of a spatial filter, which relatively increases neural processing of stimuli at relevant spatial locations and suppresses distractors. In direct support of this, we recently used an experimental paradigm to separate target selection from distractor suppression during spatial attention and found that both mechanisms independently induce lateralization of alpha power ( Wöstmann et al., 2019 ).…”
Section: Introductionmentioning
confidence: 93%